Transgenic plants as a model for studying еpigenetic regulation of gene expression - T. V. Marenkova; E. V. Deineko (Вавиловский журнал генетики и селекции)
The phenomenon of loss of expression of transferred genes in transgenic plants was discovered in the early 1990s. The study of this phenomenon revealed dependence of the frequency of gene silencing on the number of integrated copies in the plant genome, the properties of the transgene sequence itself (the presence of duplications, vector sequences, and others), chromosomal position. Loss of gene expression can occur transcriptionally or post-transcriptionally in most cases involving small interfering RNA (siRNA). In plants, the most common mechanism for inactivation of genes at the level of RNA transcription is RNA-directed DNA methylation (RdDM). An important role is played by the plant-specific RNA polymerase IV and V. Pol IV is assumed to transcribe non-coding transcripts at its target loci. They are copied into long dsRNAs and are processed by DICER into siRNAs. siRNAs are then methylated and loaded into the effector complex, whose main component is a protein of the Argonaute family. RNA polymerase V also transcribes the noncoding transcript of the target gene, but it serves as a scaf¬fold that interacts with siRNAs and that recruits proteins and enzymes responsible for DNA and histone methylation. Posttranscriptional gene inactivation occurs in the cytoplasm and is associated with a specific effector complex (AGO-siRNA), which cleavages homologous mRNA. In plants, in addition to the canonical pathway, RdDM, more mechanisms exist, which include components for posttranscriptional gene inactivation, specific proteins and other types of small RNAs. In this review, we briefly discuss the currently known components of epigenetic regulation.